Upstream stimulatory factor regulates expression of the cell cycle-dependent cyclin B1 gene promoter. - Cogswell, J P (1995)
Progression through the somatic cell cycle requires the temporal regulation of cyclin gene expression and cyclin protein turnover. One of the best-characterized examples of this regulation is seen for the B-type cyclins. These cyclins and their catalytic component, cdc2, have been shown to mediate both the entry into and maintenance of mitosis. The cyclin B1 gene has been shown to be expressed between the late S and G2 phases of the cell cycle, while the protein is degraded specifically at interphase via ubiquitination. To understand the molecular basis for transcriptional regulation of the cyclin B1 gene, we cloned the human cyclin B1 gene promoter region. Using a chloramphenicol acetyltransferase reporter system and both stable and transient assays, we have shown that the cyclin B1 gene promoter (extending to -3800 bp relative to the cap site) can confer G2-enhanced promoter activity. Further analysis revealed that an upstream stimulatory factor (USF)-binding site and its cognate transcription factor(s) are critical for expression from the cyclin B1 promoter in cycling HeLa cells. Interestingly, USF DNA-binding activity appears to be regulated in a G2-specific fashion, supporting the idea that USF may play some role in cyclin B1 gene activation. These studies suggest an important link between USF and the cyclin B1 gene, which in part explains how maturation promoting factor complex formation is regulated.